Ermenek'te Emir Musa Bey Medresesi (Tol Medrese) ve Vakfiyesi - Çiftçioğlu, İsmail (Kitabevi, 2001)
This work is concerned with the historical and artistic importance of Tol Madrasah that was commissioned by Karamanli Musa Bey in the period of Anatolian Emirates. Using the written documents of its wakf, social and cultural conditions of its period is explained. The work includes pictures of the madrasah and the building of its wakf.
Madrasah of Emir Musa and Its Wakf in Ermenek
Keywords: Art History; Anatolian Seljuks; Emir Musa Bey; Tol Madrasah